Fat and exposure to 4-nitroquinoline-1-oxide causes histologic and inflammatory changes in murine livers - Pitstick, Lenore D.; Goral, Joanna; Schmelter, Ryan A.; Fuja, Christine M.; Ciancio, Mae J.; Pytynia, Matthew; Meyer, Alice; Green, Jacalyn M. (PLOS ONE, 2022)
Risk factors for liver cancer include tobacco use, alcohol consumption, obesity, and male sex. Administration of 4-nitroquinonline-1-oxide (4NQO) in drinking water mimics the effects of tobacco and leads to oral carcinoma in mice. This study compared the effects of diets high and low in saturated fat (HF and LF, respectively), and sex, on liver histopathology in 4NQO-treated mice and controls. We hypothesized that 4NQO would cause histopathological changes in liver, and that a HF diet would increase hepatic pathology when compared to the LF diet. Mice (C57Bl/6, 36/sex), were divided into a low fat (10 kcal% fat; LF) or high fat (60 kcal% fat, HF) diet. Mice were further subdivided into one of 3 water treatment groups for 17 weeks: water (control), vehicle (1.25% propylene glycol in water [PG]), or 4NQO in (50 μg/ml; 4NQO). All mice were subsequently given water alone for 6 more weeks. Upon euthanasia, livers were harvested, fixed, sectioned, and stained with hematoxylin and eosin (H&E). H&E slides were graded for histopathology; frozen liver samples were analyzed for triglyceride content. Trichrome stained sections were graded for fibrosis. CD3+ T cells, CD68+ macrophages, and Ly6+ neutrophils were detected by immunohistochemistry. Compared to water controls, 4NQO-treatment caused mouse liver histopathological changes such as fibrosis, and increases in hepatic neutrophils, T cells, and macrophages. HF diet exacerbated pathological changes compared to LF diet. Male controls, but not females, demonstrated severe steatosis and increased triglyceride content. 4NQO treatment decreased hepatic fat accumulation, even in animals on a HF diet. In conclusion, this murine model of oral cancer may serve as a model to study the effects of tobacco and diet on liver.